Preliminary study on cutting solid object using water at pressure exceeding 1000 MPa - Ahmad Humaizi, Hilmi; Mohd Nor Azman; Ariffin, Ismail, Lt Col Assoc. Prof .; Mohammed Alias, Yusof, Prof. Madya Ir.; Ahmad Mujahid, Ahmad Zaidi, Dr.; Shohaimi, Abdullah, Brig. Jen. Prof. Madya Dr. (Trans Tech Publications, 2013)
Link to publisher's homepage at www.ttp.net/